2000
DOI: 10.1093/emboj/19.9.2069
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of Skp2 results in accumulation of cyclin E and p27Kip1, polyploidy and centrosome overduplication

Abstract: The ubiquitin–proteasome pathway plays an important role in control of the abundance of cell cycle regulators. Mice lacking Skp2, an F‐box protein and substrate recognition component of an Skp1–Cullin–F‐box protein (SCF) ubiquitin ligase, were generated. Although Skp2−/− animals are viable, cells in the mutant mice contain markedly enlarged nuclei with polyploidy and multiple centrosomes, and show a reduced growth rate and increased apoptosis. Skp2−/− cells also exhibit increased accumulation of both cyclin E … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
658
4
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 665 publications
(712 citation statements)
references
References 40 publications
49
658
4
1
Order By: Relevance
“…Skp2 is the substrate-recognition component of the SCF Skp2 ubiquitin ligase complex and is a key regulator of S-phase entry (Nakayama et al, 2000;Harper, 2002;Cardozo and Pagano, 2004). Overexpression or Regulation of RASSF1A by Skp2 at G 1 -S transition MS Song et al amplification of Skp2 has been reported in a large number of human cancers (Yokoi et al, 2002) and transgenic expression of Skp2 in mice leads to tumor formation, suggesting that Skp2 is oncogenic (Gstaiger et al, 2001;Latres et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Skp2 is the substrate-recognition component of the SCF Skp2 ubiquitin ligase complex and is a key regulator of S-phase entry (Nakayama et al, 2000;Harper, 2002;Cardozo and Pagano, 2004). Overexpression or Regulation of RASSF1A by Skp2 at G 1 -S transition MS Song et al amplification of Skp2 has been reported in a large number of human cancers (Yokoi et al, 2002) and transgenic expression of Skp2 in mice leads to tumor formation, suggesting that Skp2 is oncogenic (Gstaiger et al, 2001;Latres et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression or Regulation of RASSF1A by Skp2 at G 1 -S transition MS Song et al amplification of Skp2 has been reported in a large number of human cancers (Yokoi et al, 2002) and transgenic expression of Skp2 in mice leads to tumor formation, suggesting that Skp2 is oncogenic (Gstaiger et al, 2001;Latres et al, 2001). Skp2 targets p27, cyclin E and FOXO1 for degradation in a phosphorylationdependent manner (Marti et al, 1999;Nakayama et al, 2000;Huang et al, 2005). Here we provide several lines of evidence that RASSF1A is also targeted by Skp2 at the G 1 -S transition: (1) the level of RASSF1A during cell cycle progression is inversely related to that of Skp2; (2) Skp2 directly interacts with and ubiquitinates RASSF1A in a manner dependent on phosphorylation of RASSF1A on Ser 203 in G 1 -S transition; (3) overexpression of Skp2 results in a decrease in the cellular abundance of RASSF1A, thereby elevating cell viability and proliferation; (4) deletion of Skp2 or depletion of Skp2 increases both the level and half-life of RASSF1A as well as induces a delay in G 1 -S progression; and (5) entry into S phase is accelerated in RASSF1A -/-MEFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockout mouse models of components of the ubiquitin ligase that targets p27, Skp2 and Cks1, further elucidate p27's role in cell cycle control [26,37]. Skp2 −/− mice are smaller than littermate controls [37].…”
Section: P27 As a Tumor Suppressor In Mouse Modelsmentioning
confidence: 99%
“…Structural analysis indicates that p27 Kip1 interacts with both Cks1 and Skp2 (Hao et al, 2005). Knockout of either Skp2 or Cks1 in mice leads to increased p27 Kip1 levels (Nakayama et al, 2000;Spruck et al, 2001) and, notably, expression of Skp2 and Cks1 is enhanced in several cancers (Gstaiger et al, 2001;Latres et al, 2001;Inui et al, 2003;Shapira et al, 2004).…”
Section: Introductionmentioning
confidence: 99%